Clinical significance of thymidine kinase in Egyptian children with acute lymphoblastic leukemia - Hagag, Adel A.; Saad, Mohamed A.; Mohamed, Sohair A. (South Asian Journal of Cancer, 2015)
Background: Acute lymphoblastic leukemia (ALL) is the most common childhood malignancy, representing one-third of pediatric cancers. Thymidine kinase-1 (TK-1) is expressed in proliferating cells so elevated TK-1 indicates active tumor growth. Objective: To study the clinical significance of TK-1 in children with ALL. Patients and Methods: This study was carried out on 40 children with newly diagnosed ALL who were admitted to Oncology Unit, Pediatric department, Tanta University (26 males and 14 females) with their ages ranged from 4 to 10 years and 30 healthy children of matched age and sex as a control group. For all patients the following were done: Complete blood picture, bone marrow examination, immunophenotyping and TK-1 serum levels. Results: Mean TK-1 level was significantly higher in patients at diagnosis than controls and significantly higher in patients with unfavorable outcome than patients with favorable outcome. Mean TK-1 level was significantly higher in patients in relapse than patients in remission and controls. No significant differences in mean TK-1 level between patients in remission and controls. There were statistically significant differences in disease free survival and overall survival between patients with favorable and unfavorable outcome. Conclusion: From this study we concluded that TK is a helpful marker in diagnosis and follow-up of patients with ALL. Recommendations: Thymidine kinase-1 should be routinely assessed at diagnosis and during follow-up in ALL patients for better diagnostic and prognostic assessment and should be taken in consideration in designing future therapeutic strategies based on patients-specific risk factors.
Keywords: Acute lymphoblastic leukemia- childhood malignancies; thymidine kinase 1; Risk stratification of ALL